Lithological models of reservoir rocks for upper cretaceous deposits in East Caucasian Region - O. V. Sivalneva; A. S. Rakhmatullina; A. V. Postnikov; O. V. Postnikova; O. A. Zueva; E. K. Idrisova; V. V. Poshibaev (Georesursy, 2024)
The article describes the results of lithological and petrophysical investigations that would be a base for characterization of reservoir rocks in Upper Cretaceous deposits. These investigations include thin sections description, SEM and NMR analysis. As found that three main factors have constrained final quality of reservoir rocks: 1) depositional settings favorable for coccoliths and chalk sedimentation; 2) late diagenesis changes – compaction and recrystallization degree; 3) fracture intensity.